The livelihood strategies and use of natural resources among the ibans in rumah bangkit Rembai, Spaoh, Betong, Sarawak - Yvonne Runya, Anak Riman (University Malaysia Sarawak, UNIMAS, 2015)
This study is conducted to investigate the livelihood strategies and use of natural resources among the Ibans in Rumah Bangkit Rembai, Spaoh, Betong. It focuses on the five livelihood assets namely human, social, natural, physical, and financial capitals including the use of land, wildlife, and forest as their livelihood strategies. Specifically, this study aims to ascertain the five livelihood assets in Rumah Bangkit Rembai; to investigate the main economic activities of the community in Rumah Bangkit Rembai; to analyse the natural resources used by the community in Rumah Bangkit Rembai as means of their livelihood strategies; and to investigate in what way the longhouse dwellers in Rumah Bangkit Rembai utilise the natural resources as their livelihood strategies. Data and information are collected by using interview schedules, focus groups interviews, and Participatory Rural Appraisal (PRA) method. The Statistical Package for Social Sciences Version 20 (SPSS Statistics v20) for Windows is used to analyse the data collected via interview schedules and is participated by 30 respondents. From this study, it proves that this Iban community conducts various types of activities in order to sustain their livelihoods. All the five livelihood assets are present in this village and these assets provided a lot of impacts to the livelihoods of this community. Agricultural activities such as cultivating cash and subsistence crops including rearing livestock either for commercial or subsistence farming are their primary economic activities. In addition, the women collect jungle produces such as wild vegetables and fruits as their secondary sources of food supply and income. Today, hunting for wildlife is considered to be an occasional activity to the older adults in this village but an uncommon activity for the younger generations. However, the concept of bejalai within this community is still very active. In order to increase their standards of living, some longhouse dwellers migrated to the urban centres to obtain better education and employments. Therefore, the livelihood strategies of this community is very much affected by their surrounding environment. However, due to modernisation, the younger generations realise that they can improve their current livelihoods by venturing into non-agricultural activities.